Fresh water cercarial fauna of Trichur - Ambika Prasad Sarmah (Department of Parasitology, College of Veterinary and Animal Sciences, 1982)
An investigation on the cercarial fauna of fresh water snails in Trichur was conducted for a period of one year (1981 – 1982). Three species of snails viz. Indoplanorbis exustus (Deshayes), Lymnaea luteola f. australis and Thiara (Melanoides) tuberculata were collected from different areas in Trichur. Snails were found to thrive throughout the year if water is available. Seven different types of cercariae could be identified in the present study. They were – 1. An amphistome cercaria of the pigmentata group referable to Cercaria indica XXVI Sewell, 1922 2. An echinostomatid cercaria, further confirmed as cercaria of Hypoderaeum conoideum 3. A xiphidiocercaria resembling Cercaria indica X Sewell, 1922 4. A brevifurcate, non – ocellate, apharyngeal cercaria referable to cercaria of Schistosoma spindale 5. A longifercate cercaria referable to Cercaria hardayali Dutt, 1970 6. A gymnocephalous cercaria resembling Cercaria indica XIV Sewell, 1922 7. Amonostome cercaria comparable to Cercaria indica VII Sewell, 1922 The maximum incidence of cercarial infection in snails was found in the month of August, Mixed infection of cercariae was observed in one Indo plannorbis exustus (Deshayes) and one Lymnaea luteola f. australis snails. The emergence character and detailed morphology of all these cercariae were studied and compared with the available literature. Experimental infection to raise the adults from the larval stage of a trematode was successfully carried out using cercaria of Hypoderaeum conoideum.